Analisis Sistem Pembayaran Cash on Delivery (COD) pada Bisnis Online: Kajian Kesesuaian dengan Etika Bisnis Islami - Fata, Zainol (Journal of Islamic Economics Studies and Practices, 2024)
In recent times, online buying and selling has become a favorite choice and is in great demand among the public, especially among young people. The reason why online buying and selling is so popular is because the payment method offered to the public in online buying and selling transactions is Cash on Delivery (COD). However, from the perspective of Islamic business ethics, the application of the COD system in online business needs to be studied further. Islam has muamalah principles that must be taken into account in every economic activity, including the practice of buying and selling so that online buying and selling business people must understand the principles of muamalah in Islam. Therefore, this research will analyze the extent to which the COD payment system in online businesses is in accordance with Islamic business ethics. The approach used in this research is a qualitative descriptive approach. This research is a qualitative descriptive research that uses library study techniques as a data collection method. Through an in-depth literature review, researchers can gain a comprehensive understanding of concepts, theories, and previous research findings related to the topic being studied. The application of ethics in COD transactions must be sourced from the teachings of the Al-Quran and Hadith as the main guideline. Several ethical principles that are relevant in muamalah and can be applied in COD-based online buying and selling transactions include justice, honesty, trustworthiness and the prohibition of usury.